2020
DOI: 10.1097/md.0000000000021625
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for the treatment of dry eye

Abstract: Background: As a common ophthalmic disease, dry eye (DE) may bring several adverse effects on the quality of life for patients. In recent years, Acupuncture (AC) is becoming increasingly popular for treating DE. Thus, we conceived this systematic review aims to evaluate the effectiveness and safety of AC for DE objectively. Methods: The search results are restricted to randomized controlled trials and human studies. We will establish the inclusion criteria through discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Otherwise, after excluding trials with significant clinical heterogeneity and sensitivity analysis, a random effects model will be used. [ 11 12 ] Grading of Recommendations, Assessment, Development and Evaluation (GRADE) will be used to determine confidence in the effect estimates.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, after excluding trials with significant clinical heterogeneity and sensitivity analysis, a random effects model will be used. [ 11 12 ] Grading of Recommendations, Assessment, Development and Evaluation (GRADE) will be used to determine confidence in the effect estimates.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…The comparison can be sham Chinese herbal sachets with standard common therapy or standard common therapy without additional intervention. [ 10 – 11 ] Detailed steps will be followed as Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Acupuncture is a traditional treatment method developed in East Asia over a significant period of time and is now recognized as an important component of complementary and alternative medicine worldwide [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of ophthalmology, papers have been published on the effectiveness of acupuncture for some ophthalmologic diseases, and meta-analysis of diseases, such as dry eye syndrome, glaucoma, slowing myopia progression, amblyopia, and acute hordeolum, have been published or are in progress [2][3][4][5][6][7][8]. Recently, several studies, including meta-analysis, regarding dry eye syndrome have been reported and are in the spotlight [4,5,9].…”
Section: Introductionmentioning
confidence: 99%